2013
DOI: 10.11113/jt.v62.1372
|View full text |Cite
|
Sign up to set email alerts
|

Tahap Kemahiran Employability Pelajar Kejuruteraan dari Perspektif Majikan

Abstract: Majikan kini memerlukan pekerja yang menguasai kemahiran teknikal dan kemahiran employability. Namun kemahiran employability yang dikuasai oleh graduan institusi pendidikan tinggi masih tidak dapat memenuhi kriteria yang diingini oleh majikan terutamanya dalam bidang kejuruteraan. Kajian ini bertujuan untuk meninjau tahap kemahiran employability pelajar kejuruteraan institusi teknikal dari perspektif majikan. Kajian ini menggunakan reka bentuk kajian kuantitatif dan kaedah kajian tinjauan. Seramai 171 responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…Many researches in Malaysia revealed that fresh engineers in Malaysia are fine in technical skills but lack in non-technical skills (20,21 Table 3, they are quite similar. Based on research done by (17), Graduates were seen did not meet the market demand and expectation where they were seen as lacking of creativity, not innovative and creative, not competitive, dependent and poor in communication skills.…”
Section: Discussion and Recommendationsmentioning
confidence: 69%
“…Many researches in Malaysia revealed that fresh engineers in Malaysia are fine in technical skills but lack in non-technical skills (20,21 Table 3, they are quite similar. Based on research done by (17), Graduates were seen did not meet the market demand and expectation where they were seen as lacking of creativity, not innovative and creative, not competitive, dependent and poor in communication skills.…”
Section: Discussion and Recommendationsmentioning
confidence: 69%
“…However, not all fresh engineering graduates in Malaysia can possessed this skill outstandingly. Based on a research done Husain et al, (2013), critical thinking and problem-solving skills are at the below of the ranking compared to teamwork skill which is in the first ranking. However, as reported in NACE Job Outlook (2018), critical thinking and problemsolving skills are the most important based on employers" rating.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Critical thinking and problem-solving skills should be emphasized by higher institution because these skills are demanded by today"s industry (MOHE, 2006). Furthermore, students feel that their critical thinking and problem-solving skills are good, but the employers in the industries feel that their non-technical skills are at the intermediate level (Husain et al, 2013;Ramlee Mustapha et al, 2008). The gap between students" and employers" perception will give an impending problem for fresh engineering graduates to be hired once they are graduated (Rasul, Abd Rauf, Mansor, & Puvanasvaran, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Contemporary employers want engineering and technology students who are well-equipped with talent, technical and communication skills, spirituality, teamwork, leadership qualities, lifelong learning attributes, critical thinking and problem-solving abilities, as well as ethics and morality. Such students are capable of using their skills and talents to fit into the current global employment scenario [8]. In addition, employers also have to put up with numerous graduates who lack professional expertise, namely thosewho are less knowledgeable and training-deficient.…”
Section: Literature Reviewmentioning
confidence: 99%